CULTURAL AND INTELLECTUAL DEVELOPMENT OF STUDENTS IN THE PROCESS OF LATIN LANGUAGE LEARNING - Nigmatullaevna, Isroilova Maxsuda; Yuldashevna, Yuldasheva Dilshoda; Sobitovna, Sayfullaeva Lola (International Journal of Psychosocial Rehabilitation, 2020)
This article describes the peculiarities of teaching Latin, the theoretical and practical state of intellectual and cultural development of students in the process of teaching Latin. Based on the results of theoretical and empirical analysis, the author has developed proposals and recommendations to improve the quality of teaching Latin.